2010
DOI: 10.1007/s00198-010-1411-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral bisphosphonates are associated with reduced mortality after hip fracture

Abstract: Like intravenous bisphosphonates after hip fracture, our study suggests that oral bisphosphonates may be associated with reductions in all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 26 publications
7
81
3
4
Order By: Relevance
“…In fact, men are twice as likely to die following a hip fracture as women [10]. Beyond the obvious fracture-related benefits, three recent studies (two of which examined oral bisphos phonates) and a systematic review of randomized trials [34] have also demonstrated that mortality is reduced in those exposed to bisphosphonates even after controlling for age, comorbidity, and fracture incidence [35][36][37]. One of these studies was a longitudinal cohort of 2005 elderly LTC residents that reported oral bisphosphonate exposure was associated with a significantly reduced hazard for mortality [hazard ratio=0.73; 95% confidence interval (CI) 0.56,0.94] [37].…”
Section: Discussionmentioning
confidence: 95%
“…In fact, men are twice as likely to die following a hip fracture as women [10]. Beyond the obvious fracture-related benefits, three recent studies (two of which examined oral bisphos phonates) and a systematic review of randomized trials [34] have also demonstrated that mortality is reduced in those exposed to bisphosphonates even after controlling for age, comorbidity, and fracture incidence [35][36][37]. One of these studies was a longitudinal cohort of 2005 elderly LTC residents that reported oral bisphosphonate exposure was associated with a significantly reduced hazard for mortality [hazard ratio=0.73; 95% confidence interval (CI) 0.56,0.94] [37].…”
Section: Discussionmentioning
confidence: 95%
“…Lyles et al showed that intravenous bisphosphonate treatment in form of zoledronic acid reduced mortality after surgical hip fracture repair [38], while Beaupre et al showed that oral bisphosphonate treatment with alendronate and risedronate reduced all-cause mortality in this population [39]. Despite these findings, the majority of patients with hip fractures are only surgically treated, with little attention being paid to osteoporosis.…”
Section: Biochemical Parametersmentioning
confidence: 97%
“…(7) In a Canadian randomized 3-year follow-up study, hip fracture patients with oral bisphosphonate use had a lower mortality than those receiving no treatment (7% versus 16%). (8) Each year of treatment was associated with a 63% relative reduction in the risk of death. (8) Another Australian 5-year followup study among institutionalized hip fracture patients showed that the use of oral bisphosphonates was associated with a 27% reduction in the risk of death compared with nonusers.…”
Section: J Jbmrmentioning
confidence: 99%
“…(8) Each year of treatment was associated with a 63% relative reduction in the risk of death. (8) Another Australian 5-year followup study among institutionalized hip fracture patients showed that the use of oral bisphosphonates was associated with a 27% reduction in the risk of death compared with nonusers. (9) In a recent meta-analysis by Bolland and colleagues (10) on the effect of osteoporosis treatment on mortality, eight studies of four drugs (ie, risedronate, strontium ranelate, zoledronic acid, and denosumab) were included in the primary analysis and two alendronate studies in the secondary analysis.…”
Section: J Jbmrmentioning
confidence: 99%